Co-delivery of simvastatin and demineralized bone matrix hierarchically from nanosheet-based supramolecular hydrogels for osteogenesis. Issue 37 (1st September 2021) - Zhang, Xiao; Fan, Jiabing; Chen, Chen; Aghaloo, Tara; Lee, Min
Abstract : Supramolecular hydrogels are widely used as 3D scaffolds and delivery platforms in tissue engineering applications. Abstract : Supramolecular hydrogels are widely used as 3D scaffolds and delivery platforms in tissue engineering applications. However, hydrophobic therapeutic agents exhibit weak compatibility in hydrogel scaffolds along with aggregation and precipitation. Herein, simvastatin drugs used as BMP-2 stimulators are encapsulated into the layer space of LAPONITE® via electrostatic interactions and ion exchange efficiently, and supramolecular hydrogels could be fabricated with a self-healing, injectable and sustained drug release nature. Hydrogels encapsulated with 10 μg mL −1 simvastatin drug show good osteogenic differentiation in vitro . Moreover, the loading of demineralized bone matrix particles could enhance the capacity for osteogenesis via improving the expression of BMP-2 synergistically. The integrated hydrogels could be implanted into cranial defect sites for bone regeneration in vivo . This work provides the first demonstration of molecular and supramolecular engineering of hydrogels to load osteoinductive agents hierarchically for bone regeneration, contributing to the development of a brand-new strategy for dealing with compatibility between scaffolds and osteogenic agents.